Design of a miniature fan for industrial application - Seow, Jun Ting (2016)
This project studies on the heat transfer enhancement due to turbulent flow in the test rig. The fluid properties are set to be at a constant rate in order to achieve a fair result for all testing. The testing involved ribs installed into the conduit with a set of different configuration arrangements. The results from previous experiment shows that no aero foil and with the enhancement of tapered conduit produced better efficiency in heat transfer. However, the study of heat transfer efficiency can be further improved. Therefore the study to enhance heat transfer is being made in this project by creating turbulent flow within the conduit. The velocity and temperature of the heat sink were observed to increase or decrease depending on the arrangement of the turbulators. Experimental result shows that single turbulator configuration achieved the best heat transfer rate. The single turbulator create turbulent flow within the conduit which improved the heat transfer rate. However, the arrangement of a pair of turbulator did not improve the heat transfer rate. The arrangement of a pair of turbulator has higher temperature compared to single turbulator. The pair of turbulator has created flow blockage instead of turbulent flow. Nevertheless, the key aspect to improve heat transfer is to create turbulent flow.